PENGARUH PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS - Alfiatun Jennah; Rama Yuli (JURNAL AKUNTANSI, 2020)
The best company performance is seen in the company’s financial performance by using the rules of financial implementation properly and correctly. This study aims to determine between inventory turnover and accounts receivable turnover towards profitability partially and simultaneously on manufacturing companies listed on the Indonesia Stock Exchange in the period 2012-2017. This research was conducted to increase the company’s profitability and make the company successful in achieving its goals without any deviant actions. This type of research is quantitative descriptive using secondary data taken by Simple Random Sampling which is a sample selection where members are randomly selected randomly (all get the same opportunity to choose) where if it has been selected it cannot be selected again. The data analysis used is SPSS version 19 because the research model uses secondary data. The data is then analyzed using The Descriptive Statistical Test, Classic Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Test and Determination Coefficient Test. The results of the study prove that inventory turnover and accounts receivable turnover have a significant effect on company profitability. Therefore, companies need to increase inventory turnover and accounts receivable turnover in order to further increase the company’s profitability.